GENDER INEQUALITY IN STEM AND RENEWABLE ENERGY EDUCATION IN UGANDA: MAKERSPACES AS PATHWAYS TO GENDER-RESPONSIVE LEARNING - Al Afif, Rafat; Nikisianli, Nikoleta; Namagambe, Aidah; Kasedde , Hillary; Pfeifer, Christoph (Journal on Processing and Energy in Agriculture, 2026)
This study examines ongoing gender inequality in Uganda’s STEM and renewable energy education pipeline, set against the backdrop of severe energy poverty and gendered burdens. It highlights the societal and innovation costs of women’s underrepresentation and explores makerspaces as inclusive, practical environments. The research aims to place girls’ and women’s STEM pathways within Uganda’s energy transition and evaluate makerspaces as a catalyst for gender-responsive learning and skills development. Using a sequential explanatory mixed-methods approach, the study incorporates: (i) a focused review; (ii) empirical fieldwork at universities and the Makerere University makerspace; and (iii) three iterative Training-of-Trainers cycles, involving surveys, interviews, focus groups, observations, and artefact reviews, alongside quantitative and qualitative analyses of inclusion and pedagogy. Results reveal deeply rooted structural barriers—such as unpaid care, labour-market discrimination, and competitive cultures—that restrict women’s participation. Well-designed makerspace training enhanced technical skills, confidence, and perceived relevance; female participation increased across training rounds, although the risk of male dominance remains without targeted measures. The study recommends coordinated, multi-level actions: adopting gender-responsive pedagogy, increasing female representation and mentorship in STEM faculties, and integrating makerspaces into supportive policies and curricula to promote scalable, gender-inclusive, hands-on learning for renewable energy careers.
Keywords: gender inequality; renewable energy education; makerspaces; trainers' cycles